Experimental and statistical analysis of robotic 3D printing process parameters for continuous fiber reinforced composites - EKİCİ, BÜLENT (SAGE PUBLICATIONS LTD, 2021)
3D printing technology has gradually taken its place in many sectors. However, expected performance cannot be obtained from the structural parts with this method due to the raw material properties and constraints of Cartesian motion systems. This technology cannot replace structural parts produced by traditional manufacturing methods. In order to avoid these constraints, it is preferred to use continuous fiber reinforced polymer composites in many areas such as automotive and aerospace industries due to their low weight and high specific strength properties. These automated composite manufacturing methods currently have limited production of geometric shapes due to the need for additional molds and production as flat surfaces. To overcome all these constraints, fiberglass reinforced ultraviolet ray-curing polymer matrix composite material are selected for robotic 3 D printing process and various parameters are examined. Fiber-polymer combination and layer structure formation was examined. Scanning Electron Microscopy (SEM) images of sections of 3 D printed test samples were taken and fiber resin curing was examined. The nozzle diameter, printing speed, fiber density and Ultra Violet (UV) light intensity parameters, which will provide effective 3 D printing process, are optimized with the Taguchi method. Tensile strength, flexural strength and izod impact values are considered as result parameters for optimization. It was found that it would be appropriate for 3D printing with a 1.0 mm nozzle diameter, 600 tex fiber density, 4 UV light, 600 mm/min printing speed. With these 3D printing process parameters, approximately 125 MPa tensile strength and 450 MPa flexural strength can be obtained. With this study, support and contribution was provided to researchers, composite producers, tool manufacturer and literature who want to use and develop this 3D printing process.
Keywords: 3D printing; composite; fiber glass; robotic; additive manufacturing; CARBON-FIBER